The Influence of Competence and Work Ethic on Teachers' Career Development at SMK Pelita Ciampea 2 - Siti; Istirhamiyah (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the influence of competence and work ethic on teachers' career development at SMK Pelita Ciampea 2. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 50 teachers. Data analysis uses the Partial Least Squares-Structural Equation Modeling (PLS-SEM) model. The results show that competence and work ethic have a positive and significant impact on teachers' career development. Good competence enhances professionalism, while a strong work ethic drives motivation and dedication in teaching. The implication of this study is the importance of schools improving teacher training and creating a supportive work environment to encourage career development.